INFANT MORTALITY REDUCTION POTENTIAL IN RUSSIA - E.V. Dubrovina ("Paediatrician" Publishers LLC, 2006)
In Russia, along with the positive trends for infant mortality reduction there is the general mortality growth dependent on external reasons and unclearly indicated states. Special examination of the infant's death circumstances showed that the social portrait of families, in which they died both of injuries and unclearly indicated states was the following - these were extremely troubled, marginal and half marginal families. This is why, the dynamics of infant mortality dependent on external reasons and unclearly indicated states may be considered as the peculiar marker of the social trouble. The growth of the number of waifs and neglected children in Russia, who are about to reach the childbearing age in the nearest future, may lead to the growth of infant mortality. Key words: infant mortality, children.